Finite Elements Method Investigation of Plates with Varied Support and Opening for Design Optimization - Faqih Ma arif; Zhengguo Gao; Eva Fatimah; Putri Nabila; Anna Rizti Pertiwi; Apri Ana Puji Astuti; Afif Fadhlih Rahardika; Azizah Nur Rohmah (Kadiri University, 2023)
Plates have an important function in supporting the structural load above them. One important aspect of plate design is the design of the openings or holes. These openings can be needed for various purposes, such as pipe installation, ventilation, and ducts. If the plate openings are not designed carefully, it will cause serious problems such as excessive deflection. This increases the risk of structural accidents and ultimately threatens the safety of building users. This study aims to determine the effect of plates with different types of supports and opening models with 3D modeling. Quantitative descriptive research using the finite element method was used. There are 16 models with different support types (simply and fixed) and opening models (rectangular, square and circular). From the modeling, the deformation and stress values that occur will be obtained. Comparative analysis is carried out to obtain the best support and opening types. The research results show that the increase in stress concentration tends to be higher in rectangular openings, while in square and circular openings, it is smaller than in plates without openings. Circular shapes tend to have high deformation values. Meanwhile, the square shape has the smallest value compared to all models. Simply support has greater stress in rectangular and circular openings. 4-sided fixed support is the best choice because it has the smallest stress and deformation values. Through these results, it is possible to optimize the design of appropriate types of supports and openings to reduce excess stress and improve overall structural performance.